Pré-tratamentos físico-químicos e digestão anaeróbia da palha de sorgo sacarino - Rossi, Eduardo de (2019)
The lignocellulosic structure of sorghum straw is the main obstacle for its anaerobic digestion. Thus, the first experiment, in laboratory scale, was carried out to study the effect of pretreatments on the chemical composition of the material. Two forms of pretreatments were determined, with NaOH:Urea and with citric acid. Factorial 23 DCCR was used, with 3 central points and 6 axial points. In the pretreatment with citric acid solubilized phenolic and aromatic compounds, determining as best when 90 g L-1 citric acid, 36 min and 49 s in autoclave and 100 g L-1 of straw were used. In the alkaline pretreatment, o-p-dihydroxyphenyl, p-p-dihydroxystyrene and phenolic styrene were characterized with better condition when applied 90 and 95 g L-1 of straw, -11.6 °C. Using this data, in the second work a mixture of pretreatment sorghum straw under the conditions determined in the first work and straw without pretreatment were evaluated. The simplex-centroid model was used to delimit the mixtures. The pretreatment of sorghum straw resulted in an increase in biogas production, SV consumption, compared to the application of straw in natura. The use of mixtures presented a synergistic effect on biogas production in all periods tested. The ideal blend, composed of pretreated straws up to 31 days TDH, varied from 33.33 to 50.00% of pretreated straw with NU and the remainder with pretreated straw with CA, 50.00 to 66.67%. After this period, mixtures containing all three components are desirable, such as at 46 days, with application of 25% IN straw, 30% pretreated CA straw, and 45% pretreated NU straw. At 61 days, factors such as rSV and % of methane were no longer significant, especially in relation to the 20 and 31 days of TDH, in which the dependent factors presented significance.It was possible to identify the best pretreatment condition with citric acid, as well as with NaOH:Urea within the limits tested. In addition to directing the application of these and sorghum straw in natura in various mixtures, depending on the TDH to be used in the reactor.